Barriers and enablers towards integrated care for survivors of sexual violence in humanitarian settings: A real-time qualitative Delphi study - Engy Sawah; Karina Kielmann; Joris Michielsen (Global Public Health)
In humanitarian settings with high levels of sexual violence (SV), care is often offered through fragmented silos, exacerbating the burden on the health workforce and survivors. We aimed to identify contextual and health systems barriers and enablers to providing integrated medical and mental health & psychosocial support (MHPSS) in the care for SV survivors in humanitarian settings. Using Valentijn’s framework, a qualitative, real-time Delphi study (RTD) approach was conducted with 17 experts representing seven geographical subregions. Challenges and enablers identified across the participants’ contexts were consistent. Contextual challenges included volatile contexts, collapsed health systems, and insufficient basic infrastructure. Professional-related challenges included lacking expertise among healthcare professionals (HCPs), high staff attrition rates, and compassion fatigue. Health systems-related challenges included poor referral and coordination mechanisms, lack of funding and resources, misaligned donor priorities and low prioritisation of SV comprehensive care. Effective networking, community engagement, capacity building, co-locating services, participatory management, promoting employees’ sense of ownership, establishing a digital information system, and a unified joint patient file were key identified enablers. Further research should be conducted to assess HCPs’ and SV survivors’ perceptions and experiences of how best to integrate MHPSS services, and understand the challenges and opportunities in delivering integrated services.